MENINGKATKAN PROFESIONALISME GURU MEMBUAT RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI SUPERVISI BIMBINGAN PRIBADI DI SDN 91/IX RENGAS BANDUNG - Muhammad Basri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The urgency of research is there are still many teachers who find it difficult to develop, establish, to adjust, and then set up to make the Learning Implementation Plan, the right one and according to the characteristics of teaching materials, the nature of teaching materials and student development in general. The purpose of this study is to improve the professionalism of teachers to make lesson plans through supervision of personal guidance. This type of research is the School Action Research which consists of four main stages namely planning, action, observation, the research subjects consisted of 11 teachers from SDN 91 / IX Rengas Bandung, which consisted eight civil governent of teachers and three governent of teacher contract. The success criteria is a percentage of 85% in general and individually. The results showed that the total score of 39.09 in the first cycle increased significantly to 44.55 in the second cycle, the percentage of success of teachers 78.18% in the first cycle increased to 89.09% in the second cycle. The results obtained in the second cycle means that the achievement of teacher professionalism makes the implementation plan of learning by 85% in general or individually, therefore, it can be concluded that the supervision of personal guidance can improve the professionalism of teachers to make a Learning Implementation Plan at SDN 91 / IX Rengas Bandung